The Characteristic and Antibacterial Activity of Nanosilver Biosynthetic using Sweet Orange - Ermawati, Dian Eka; Putro, David Sarono; Amaris Susanto, Nindita Clourisa (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2023)
Sweet orange contains citric acid and ascorbic acid that act as a silver ion bioreducer to form nanosilver (AgNPs). Silver ion green synthesis using sweet orange peel resulted in smaller particle sizes than C. lemon and C. limeta. Therofore, this study aims to determine the characteristic of nanosilver biosynthetic using sweet orange bioreductor and antibacterial activity. Silver nitrate solution of 1.0 mM was mixed with sweet orange juice - peel infusion in ratio of 3.0: 0.0; 1.5: 1.5; and 0.0: 3.0 mL. The process was conducted using a water bath at 60 ˚C for 45 minutes. The formation of AgNPs is indicated by a color change from colorless to yellowish-brown using UV/Vis spectrophotometer and PSA. The stability test of AgNPs is determined for 30 days storage at room temprature and their antibacterial activity against S. aureus and S. epidermidis. The results showed that sweet orange juice accelerated the color change at the SPR range of AgNPs at 438-459 nm, but it is less stable. The mix solution of sweet orange juice and sweet orange peel infusion of 1.5: 1.5 mL are stable and promising as an antibacterial agent. Futhermore, the AgNPs produced had a particle size of 41±10 nm and a spherical shape.